+0  
 
+6
229
1
avatar+152 

Explain this to me please.

\(\frac{m-3}{4}=\frac{m+1}{3}\)

xRainexSiderisx  Mar 9, 2017

Best Answer 

 #1
avatar+86890 
+10

[m - 3] / 4   = [m + 1 ] / 3        cross-multiply

 

3 [ m - 3 ]  = 4 [ m + 1]       simplify

 

3m - 9    =  4m + 4     add 9 to both sides, subtract 4m from both sides

 

-1m   =  13          divide both sides by -1

 

m = -13

 

 

cool cool cool

CPhill  Mar 9, 2017
 #1
avatar+86890 
+10
Best Answer

[m - 3] / 4   = [m + 1 ] / 3        cross-multiply

 

3 [ m - 3 ]  = 4 [ m + 1]       simplify

 

3m - 9    =  4m + 4     add 9 to both sides, subtract 4m from both sides

 

-1m   =  13          divide both sides by -1

 

m = -13

 

 

cool cool cool

CPhill  Mar 9, 2017

15 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.